THE HISTORICAL AND CULTURAL CONTEXT OF THE GRASSFIELDS: A DETERRENT TO VIOLENCE IN SECONDARY SCHOOLS OF CAMEROON 2015-2022 - Dzeawoni , Atlee (American International Journal of Social Science Research, 2025)
Violence in the school environment involves behavior that is anti-social and is evidenced by undesirable tension, chaos, insults, bullying, sexual harassment, mockery, jostling, and fighting. Studies reveal that a higher percentage of these acts occur amongst learners. The problem is that scholars disagree on the definition of a violent act in school, specifically, when and how such an act is considered to begin. This study examines the socio-cultural and historical context of the Grassfields of Cameroon. It singles out elements that deter learners from committing violent acts against their mates, teachers, parents, and older people. It employs a Qualitative approach. Its findings are based on survey data on cases of violence in Cameroonian schools from 2015 to 2022. It argues that the historical and cultural context of the Grassfields region favors peace, respect, and restraint, which accounts for the limited cases of violence by learners against their peers, school authorities, parents, and guardians. Its significant findings suggest that instances of spectacular violence seldom occur in the Grassfields. It also reveals that violence against parents and teachers increased during seasons of income-generating activities in rural areas. It concludes that the historical and cultural context of the Grassfields of Cameroon deters violence, promotes harmony, and respect for constituted authority. The paper recommends that national cultures, categorized by various cultural zones, be taught in Cameroonian schools, with an emphasis on the positive elements that promote non-violence. JEL Classification Codes: I28.